Style and quality of life of Medical students in the state of Sergipe (Research, Society and Development, 2023)
Lifestyle is characterized by identifiable patterns of behavior that can have a profound effect on the health of the population and is related to several aspects that reflect attitudes, values ​​and opportunities in people's lives. Therefore, it is necessary to develop habits healthy lifestyle, with the practice of physical activities and a good diet, linked to good social relationships, safe sex, not consuming alcohol and drugs, in addition to controlling stress and anxiety. In university students, particularly those studying Medicine, the intense course load, the reduction in leisure activities and social interaction, the extensive content, added to the frequent contact with illnesses and death, favor a compromised quality of life. This article is a cross-sectional and quantitative study with data collection using a form. carried out with medical students from the state of Sergipe, which aims, therefore, to evaluate the impact on the quality of life and health of medical students during their graduation, using a self-administered questionnaire called “Fantastic Lifestyle”, linked to variables such as age, student period, sex, previous psychiatric diagnosis and use of psychoactive drugs.